Factors influencing fruit and vegetable consumption behaviour of urban adults in Malaysia - Othman, Khairunnisa Izzati (2014)
Fruits and vegetables are an important part of a healthy diet because they contain low energy density and sources of micronutrients, fibres and other components of functional properties. Despite the benefits of fruits and vegetables, the consumption among Malaysian adults is still low due to lack of public knowledge’s on the fruits and vegetables benefits. Thus, an appropriate influential factors need to be identified and considered to increase the consumption of fruits and vegetables in Malaysia. Notwithstanding, there is a dearth of literature on fruits and vegetables, purchasing behaviour and the factors influencing the consumption behaviour. Therefore, this study aims to narrow down the gap by identifying factors that influenced fruits and vegetable consumption and purchasing behaviour. Subsequently, the study was designed to meet four proposed objectives. Firstly, the study aimed to determine the significant relationship on personal factors towards adult’s intention to consume fruits and vegetables. The second objective was to determine the significant relationship on environmental factors towards adult’s intention to consume fruits and vegetables. Further, the third objective was to analyse the significant mean differnces of socio demographic factors towards adult’s intention to consume fruits and vegetables. Finally, the fourth objective was build to compare the consumption pattern and purchasing behaviour of different socio-demographic factors. A quantitative study by using a survey questionnaire was chosen because it is accurate in measuring the attitude, behaviour and identifies the relationship of factors involved. The study was supported by Social Cognitive Theory. Malaysian adult aged between 18 to 59 years old were selected based on convenience sampling in selected cities in shopping complexes in Malaysia. Subsequently, the proportion was made to identify the accurate number of adults. Out of 1200 questionnaires were distributed, 1049 were useable and the response rate was 87.4%. Data were analysed by using Factor Analysis, Multiple Linear Regressions, Independent Sample T-Test, and one-way ANOVA to answer the research objectives The findings revealed that attitude, habit, social influences, and availability have significant relationship fruits and vegetables consumption behaviour. Females were found to have higher interest than their male counterpart in all those predictors. It indicates that females were more health conscious than men. Results found that the most preferred fruits among adults in Malaysia were apple, banana, orange, watermelon, and papaya. Meanwhile, chilli, cabbage, cucumber, mustard leaf, tomatoes, and water convolvulus were the most frequently consumed vegetables. It was also noted that Malaysian adults commonly purchased fruits and vegetables in supermarkets. It is proposed that, in increasing the production and supply of higher demand fruits to increase the availability and continuous supply of fruits and vegetables. By segmenting the fruits and vegetables markets among adults based on the influencing factors, empirical and theoretical suggestions can be useful for marketers and stakeholders. They can consider the consumer profile on likely to consume the different types of fruits and vegetables in selected cities and determining the potential type of fruits and vegetables that will be marketed in selected areas. Meanwhile, health authorities can use the findings to improve future policies in fruits and vegetables in order to promote and facilitate greater fruits and vegetables consumption.